The Oxford handbook of hoarding and acquiring - Frost, Randy O.; Steketee, Gail; Nathan, Peter E. (Oxford library of psychology., 2014)
The Oxford Handbook of Hoarding and Acquiring is the first volume to detail the empirical research on hoarding.